2010
DOI: 10.1111/j.1540-6210.2010.02222.x
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Business Improvement Districts: A New Governance Framework

Abstract: What is the current state of research on business improvement districts (BIDs)? What is an appropriate framework for analysis? What are key questions for advancing future BID research? BIDs can be understood best within a network governance framework. The research shows, first, a blurring of the line between the public and private spheres as a result of BIDs; second, BIDs are increasingly important actors in urban governance; third, BIDs engage in collaborative, conflictual, and co‐optative relations with loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 31 publications
2
29
0
6
Order By: Relevance
“…Yukarıda da belirtildiği gibi, HİB yönetimlerinin tek başlarına değil, belediyeler, diğer yönetim birimleri ve bölgelerindeki özel kuruluşlar ile birlikte çalışmaları, yapılan işlerde kimin ne kadar sorumlu olduğunu karmaşıklaştırmaktadır. Morçöl ve Wolf (2010) Gün geçtikçe artan ve gittikçe karmaşıklaşan çağdaş kent sorunlarını belediyelerin, esnafın, esnaf derneklerinin ya da kâr gözet-meyen diğer kuruluşların tek başlarına çözmeleri mümkün değildir. Yeni mekanizmalara ve yeni ortaklıklara ihtiyaç vardır.…”
Section: Hizmet İyileştirme Bölgelerine Yönelik Eleştirilerunclassified
“…Yukarıda da belirtildiği gibi, HİB yönetimlerinin tek başlarına değil, belediyeler, diğer yönetim birimleri ve bölgelerindeki özel kuruluşlar ile birlikte çalışmaları, yapılan işlerde kimin ne kadar sorumlu olduğunu karmaşıklaştırmaktadır. Morçöl ve Wolf (2010) Gün geçtikçe artan ve gittikçe karmaşıklaşan çağdaş kent sorunlarını belediyelerin, esnafın, esnaf derneklerinin ya da kâr gözet-meyen diğer kuruluşların tek başlarına çözmeleri mümkün değildir. Yeni mekanizmalara ve yeni ortaklıklara ihtiyaç vardır.…”
Section: Hizmet İyileştirme Bölgelerine Yönelik Eleştirilerunclassified
“…This change poses a huge challenge from the point of view of local governance as it requires tight collaboration between public and private agents, which demands clearly defined and designated powers and responsibilities (Villarejo, 2014). A new model of governance that incorporates these challenges is therefore needed (Morçöl & Wolf, 2010). A new form of public-private collaboration within the sphere of local government has been proliferating in North American cities for over four decades, from where it has spread to many other countries.…”
Section: New Forms Of Urban Governance In XXI Century Cities: Businesmentioning
confidence: 99%
“…In response, researchers have analyzed the Different Perspectives on City Competitiveness 36 expanded relations of BIDs to their local governments (e.g., Morçöl & Wolf, 2010;Wolf, 2008). These studies indicate that BIDs are both autonomous and interdependent with governments, and suggest that governments are becoming more dependent on BIDs with them taking over more responsibilities for service delivery, and the legal and de facto governmental authority they exercise (Mitchell, 2008).…”
Section: City Levelmentioning
confidence: 99%
“…The prevalence of collaboration in BID-government relationships might not be surprising, because quite often the two parties share the common purpose of economic revitalization. However, the few studies that have analyzed BID-government relationships usually neglect the public side and focus on the private dimension of the partnership (S. Grossman, 2008 paradigms that examine all for-profit and nonprofit organizations involved in public policy making and service delivery to offer a better understanding of the type of relationships and power differentials among BIDs, between government and BIDs, and the centrality of BIDs in relation to other actors (Lewis, 2010;Morçöl & Patrick, 2006;Morçöl, Vasavada & Kim, 2014;Morçöl & Wolf, 2010;Morçöl & Zimmermann, 2006). Morçöl et al (2014) found in their longitudinal case study in downtown Philadelphia that the director of the BID, the city council, and mayors were the most central actors in the governance network, with the BID director being more central than other legally sanctioned actors.…”
Section: City Levelmentioning
confidence: 99%
See 1 more Smart Citation